2015
DOI: 10.1073/pnas.1423695112
|View full text |Cite
|
Sign up to set email alerts
|

Induced transcription and stability of CELF2 mRNA drives widespread alternative splicing during T-cell signaling

Abstract: Studies in several cell types have highlighted dramatic and diverse changes in mRNA processing that occur upon cellular stimulation. However, the mechanisms and pathways that lead to regulated changes in mRNA processing remain poorly understood. Here we demonstrate that expression of the splicing factor CELF2 (CUGBP, Elav-like family member 2) is regulated in response to T-cell signaling through combined increases in transcription and mRNA stability. Transcriptional induction occurs within 6 h of stimulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 69 publications
5
77
0
Order By: Relevance
“…3A and B). Consistent with previous observations (29,30), we found CELF2 expression to be increased upon T cell activation ( Fig. 3C) providing a possible explanation for increased binding in our cross-link assays.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3A and B). Consistent with previous observations (29,30), we found CELF2 expression to be increased upon T cell activation ( Fig. 3C) providing a possible explanation for increased binding in our cross-link assays.…”
Section: Resultssupporting
confidence: 93%
“…This idea is consistent with the recent finding that overexpressing human CELF2 in mouse heart leads to substantial changes in the global splicing pattern; among the potential target exons found in this study was TRAF3 exon 8, which was not found when overexpressing CELF1 (28). It should be noted, however, that there is only little overlap between the exons regulated by CELF2 overexpression in the heart and CELF2 knockdown in T cells (28,30), which may indicate a tissue-specific regulation of CELF2 activity. One possibility is alternative splicing of CELF2 itself (27,39), which, based on reference sequences, gives rise to many different isoforms.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations